Al-Fatāwā al-‘Ālamgīriyyah: Ḥanafī Legal Code of the Mughal Empire - Abbasi, Muhammad Zubair (Islamic Studies, 2020)
Al-Fatāwā al-‘Ālamgīriyyah is a significant contribution of Indian Muslim jurists to the corpus of the Ḥanafī school. It was a compendium of the Ḥanafī authoritative rulings. At the behest of the Mughal Emperor, Aurangzēb ‘Ālamgīr, a board of jurists from various parts of India worked jointly to produce this compendium of Ḥanafī fiqh. It closely followed the Ḥanafī legal tradition by adopting the scheme of chapters of the famous Ḥanafī treatise, the Hidāyah and contributed to the legal literature by including various chapters on legal practice and procedural law. The analysis of the contents of al-Fatāwā al-‘Ālamgīriyyah and contemporary historical evidence suggests that it performed the functions of a legal code in the historical context in which it was compiled though it was not the exclusive source of legal norms in the administrative structure of the Mughal Empire.